Hyperprolactinemia and Hypopituitarism in Acromegaly and Effect of Pituitary Surgery: Long-Term Follow-up on 529 Patients - Guo, Xiaopeng; Zhang, Ruopeng; Zhang, Duoxing; Wang, Zihao; Gao, Lu; Yao, Yong; Deng, Kan; Bao, Xinjie; Feng, Ming; Xu, Zhiqin; Yang, Yi; Lian, Wei; et al. (Frontiers in Endocrinology, 2022)
Purpose: Studies on hyperprolactinemia and hypopituitarism in acromegaly are limited. We aimed to analyze the preoperative status, postoperative alterations, and correlated factors of hyperprolactinemia and hypopituitarism in acromegaly patients. Methods: This is a single-center cohort study with long-term follow-up. We prospectively enrolled 529 acromegaly patients. Hyperprolactinemia and hypopituitarism were evaluated by testing hypothalamus-pituitary-end organ (HPEO) axes hormones before and after surgery. Results: Hyperprolactinemia (39.1%) and hypopituitarism (34.8%) were common in acromegaly. The incidences of axis-specific hypopituitarism varied (hypogonadism, 29.7%; hypothyroidism, 5.9%; adrenal insufficiency, 5.1%), and multiple HPEO axes dysfunction was diagnosed in 5.3% of patients. Patients with preoperative hyperprolactinemia (hazard ratio [HR]=1.39 [1.08-1.79]; p=0.012), hypogonadism (HR=1.32 [1.01-1.73]; p=0.047), and hypothyroidism (HR=3.49 [1.90-6.44]; p<0.001) had higher recurrence rates than those without. Age, sex, body mass index, tumor size, invasiveness, prolactin staining, ki-67 index, and GH/IGF-1 levels were significantly correlated with preoperative hypopituitarism and hyperprolactinemia. At median 34-month follow-up after surgery, hyperprolactinemia in 95% and axis-specific hypopituitarism in 54%-71% of patients recovered, whereas new-onset hypopituitarism (hypogonadism, 6.2%; hypothyroidism, 4.0%; adrenal insufficiency, 3.2%) was also diagnosed. A shorter tumor diameter was associated with the normalization of preoperative hyperprolactinemia after surgery. Cavernous sinus non-invasion, a shorter tumor diameter, cure at follow-up, and a lower GH nadir level were associated with the improvement of preoperative hypopituitarism after surgery. A larger tumor diameter was associated with the newly-developed hypopituitarism after surgery. Conclusion: Hyperprolactinemia and hypopituitarism are common among acromegaly patients and predict worse surgical outcomes. After surgery, improvement and worsening of HPEO axes function co-exist. Correlated factors are identified for clinical management.